(untitled) (Advances in Applied Biological Research, 2024)
Chronic Kidney Disease, Ayurveda, Mutraaghaata symptoms significantly improved. The patient’s key laboratory parameters, such as serum creatinine, urea, and serum uric acid, also showed marked improvement, trending toward normal levels at the time of discharge. The treatment regimen included Ayurvedic oral medications like Tab. Asthipurak, Tab. Chander Vati, Renal Support syrup, and GFR powder, complemented by Panchakarma procedures such as Awgaha Swedan, Matra Basti, Kashaya Basti, and Shiroabhyanga. The results of this case indicate that Ayurvedic interventions can lead to significant improvements in both biochemical markers and clinical symptoms in patients with Stage V CKD. These findings suggest that Ayurveda may offer a promising complementary or alternative approach to conventional CKD treatment, highlighting the need for further research in this area